Effect Of Paclobutrazol And Summer Pruning On Yield And Fruit Quality Of Apple Cv. ‘red Delicious’ (Applied Biological Research, 2015)
The study was aimed to assess the effect of different levels of paclobutrazol  and summer pruning on fruit quality of apple cv. ‘Red Delicious’. The  experiment was conducted at SKUAST-K, Shalimar (J&K) during 2012  and 2013 on apple trees of >15 years age, spaced at 5.49 × 5.49 m distance.  The experiment was laid in a completely randomized block design with  paclobutrazol spray tested at 3 concentrations (250, 500 and 750 ppm) and  summer pruning at 2 timings (8 and 12 weeks after full bloom) and their  combinations. Highest yield of 101.0 kg tree-1 was obtained in treatment  750 ppm paclobutrazol + 2 summer prunings in comparison to control. In  addition, it significantly improved fruit size (53.15 cm), weight (188.19 g),  volume (188.12 cm3), colour change (3.40 score), firmness (11.98 kg cm-2),  organoleptic rating in terms of taste (3.14 score), texture (3.24 score),  flavour (3.12 score) and total soluble solids (14.47oB) whereas acidity  (0.23%) was reduced in comparison to control and other treatments  during both the years.
Keywords: Apple; fruit quality; fruit firmness; paclobutrazol; summer pruning; yield